ANALYSIS OF ROAD DAMAGE USING THE PCI (Pavement Condition Index) METHOD AND ALTERNATIVE HANDLING (Case Study : Jl. Raya Dumaja - Jl. Raya Tanah Merah, Kab. Bangkalan STA 32+000 - 35+000) - Majid, Abd.; Fatmawati, Laily Endah (Fakultas Teknik Universitas Tanjungpura, 2023)
The highway is an essential facility for the community to achieve its goal, so the community needs a safe and convenient road, and it is expected to improve the industry and the economy of the community. However, over time, the condition of the highway will decrease according to the age of the road, and it will be an obstacle for their trip. This research is conducted to see the condition of the damaged surface flexible stiffening in Jl. Raya Dumaja - Jl. Raya Tanah Merah, Kab. Bangkalan. The method used in this study is the PCI (Pavement Condition Index) method to evaluate road stiffening by type, level, and level of damage that occurs, as well as a reference and maintenance effort. The result of this research based on the PCI method is JL. Raya Dumaja -Jl. Raya Tanah Merah STA, 32 + 000 - 35 + 000, gets a total score of 53.68 medium (Fair) with a PCI percentage of the highest road conditions is 45% in good road conditions (Good), 38.3% in medium road conditions (Fair), 15% in bad road conditions (Poor) and very bad (Very Poor), 1.67% with the alternative handling is the treatment of abilities.